The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fphys.2021.786255
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Acute Respiratory Distress Syndrome

Abstract: Acute respiratory distress syndrome (ARDS) is a devastating clinical syndrome that leads to acute respiratory failure and accounts for over 70,000 deaths per year in the United States alone, even prior to the COVID-19 pandemic. While its molecular details have been teased apart and its pathophysiology largely established over the past 30 years, relatively few pharmacological advances in treatment have been made based on this knowledge. Indeed, mortality remains very close to what it was 30 years ago. As an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 448 publications
(648 reference statements)
0
8
0
Order By: Relevance
“…Even in patients who survive ALI, there is evidence that their long-term quality of life is adversely affected. The cellular characteristics of ALI include excessive transepithelial neutrophil migration into the alveolar and interstitial spaces, loss of alveolar-capillary membrane integrity, the release of pro-inflammatory and cytosolic mediators such as interleukin (IL-6), IL-1β, and tumor necrosis factor (TNF), and upregulation of nuclear factor kappa B (NF-κB) and mitogen-activated protein kinases (MAPK) signaling pathways [11,12]. Several studies have shown that, following infection or injury to the lung tissues, plasma levels of pro-inflammatory cytokines can increase significantly (cytokine storm), leading to dysfunction and subsequent failure of multiple organs [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Even in patients who survive ALI, there is evidence that their long-term quality of life is adversely affected. The cellular characteristics of ALI include excessive transepithelial neutrophil migration into the alveolar and interstitial spaces, loss of alveolar-capillary membrane integrity, the release of pro-inflammatory and cytosolic mediators such as interleukin (IL-6), IL-1β, and tumor necrosis factor (TNF), and upregulation of nuclear factor kappa B (NF-κB) and mitogen-activated protein kinases (MAPK) signaling pathways [11,12]. Several studies have shown that, following infection or injury to the lung tissues, plasma levels of pro-inflammatory cytokines can increase significantly (cytokine storm), leading to dysfunction and subsequent failure of multiple organs [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches in drug design and ALI/ARDS treatment are required. Gene-targeted strategies for ALI/ARDS cure primarily focus on alveolar fluid clearance (AFC), alveolar capillary barrier function (ACBF), and pulmonary inflammation [ 25 , 26 ]. Enhancing AFC and restoring ACBF implies gene delivery (e.g., Na + , K + -ATPase β1 subunit) [ 25 ], while targeting pulmonary inflammation can be carried out by both gene delivery and gene silencing.…”
Section: Introductionmentioning
confidence: 99%
“…Gene-targeted strategies for ALI/ARDS cure primarily focus on alveolar fluid clearance (AFC), alveolar capillary barrier function (ACBF), and pulmonary inflammation [ 25 , 26 ]. Enhancing AFC and restoring ACBF implies gene delivery (e.g., Na + , K + -ATPase β1 subunit) [ 25 ], while targeting pulmonary inflammation can be carried out by both gene delivery and gene silencing. The first strategy is to promote anti-inflammatory effects and implies the induction or delivery of anti-inflammatory cytokines, anti-oxidant enzymes, and other protective proteins, including IL10 [ 27 ], IL12 [ 28 ], superoxide dismutases (SODs) [ 29 ], heme oxygenase-1 (HO-1) [ 30 ], prostaglandins (PGs) synthase [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute respiratory distress syndrome (ARDS) is a dangerous and life-threatening pathological condition which prevents enough oxygen from getting into the lungs and blood, serving as a serious and medical problem urgently needed solving [1]. In addition to bacterial and viral pneumonia, some nonpulmonary sources involving aspiration of gastric contents, severe trauma, drug reaction, and pancreatitis are all related with the development of ARDS [2][3][4]. The Berlin definition diagnostic criteria for ARDS involve arterial hypoxemia with PaO 2 /FiO 2 ratio < 300 mmHg and bilateral infiltrates without cardiogenic pulmonary edema on chest imaging [5].…”
Section: Introductionmentioning
confidence: 99%